1995
DOI: 10.1016/0920-9964(95)95115-p
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive fitness in familial schizophrenia

Abstract: Background-Reproductive fitness is an important factor in understanding inheritance in genetic disorders. The purpose of this study was to determine whether fitness is reduced in familial schizophrenia (FS) and if fitness in siblings differs from the norm.Method-The number of offspring in 36 subjects with RDC schizophrenia or schizoaffective disorder (SZ) and their 101 siblings from large FS families was compared with age-adjusted census figures.Results-Fitness in the SZ group was significantly reduced: 23% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 31 publications
7
43
1
1
Order By: Relevance
“…A mechanism that included a high rate of spontaneous mutations predisposing to schizophrenia would be consistent with the low rate of family history of schizophrenia usually found in individuals with the illness, and apparently "sporadic" schizophrenia [26]. The authors have previously pointed out how a high rate of spontaneous mutations could help explain the maintenance of the illness prevalence despite low reproductive fitness [54]. The possibility of spontaneous mutations reemphasizes the idea, also noted previously, that "genetic" does not equate with "inherited.…”
Section: Insight #3: New Evidence For An Old Idea-spontaneous Mutatiomentioning
confidence: 97%
“…A mechanism that included a high rate of spontaneous mutations predisposing to schizophrenia would be consistent with the low rate of family history of schizophrenia usually found in individuals with the illness, and apparently "sporadic" schizophrenia [26]. The authors have previously pointed out how a high rate of spontaneous mutations could help explain the maintenance of the illness prevalence despite low reproductive fitness [54]. The possibility of spontaneous mutations reemphasizes the idea, also noted previously, that "genetic" does not equate with "inherited.…”
Section: Insight #3: New Evidence For An Old Idea-spontaneous Mutatiomentioning
confidence: 97%
“…It is substantially heritable (Gottesman 1991;Cardno et al 1999), though what is inherited is best described as a diathesis or vulnerability that may or may not lead to actual illness, and whose progression is affected by environmental factors . Many studies have shown that schizophrenia is associated with impaired physical health (Brown et al 2000), and drastically reduced probability of reproduction (Bassett et al 1996;Avila et al 2001). This naturally raises an evolutionary puzzle.…”
Section: Introductionmentioning
confidence: 99%
“…20 The relative reproductive fitness associated with TOF was assessed using 2 standard proxies: the mean number of liveborn offspring per proband and the proportion of probands who were childless. 13,21 The comparison group consisted of Canadian adults with neither CHD nor 22q11.2 deletions, used in a previous study of reproductive fitness and representative of men and women in the general population. 13 The TOF group and the comparison group were well matched with respect to age and birth cohort.…”
Section: Analysesmentioning
confidence: 99%